A case of long-term survival after multimodal local treatments of intramedullary spinal cord metastasis of squamous cell lung cancer - Minomo, Shojiro; Tokoro, Akihiro; Utsumi, Tomoki; Ishihara, Masahiro; Akira, Masanori; Atagi, Shinji (Journal of Thoracic Disease, 2016)
Intramedullary spinal cord metastasis of non-small cell lung cancer is rare, and it has a short prognosis. We report a 53-year-old man diagnosed with cT4N0M0, stage IIIA squamous cell lung cancer. Ten months after left pneumonectomy (pT4N0M0), an intramedullary spinal cord tumor developed at the axis level. The intramedullary spinal cord tumor was resected, and he was diagnosed with metastatic squamous cell lung cancer. Radiotherapies and another tumor resection were conducted, as he had a good performance status and the discrete lesion was associated with the risk of brain stem compression. Multimodal local treatments for intramedullary spinal cord metastasis caused the tumor to shrink, and he lived for 25 months after the spinal metastasis occurred.